2017
DOI: 10.1002/cncr.31146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic hepatitis C virus infection on the survival of patients with oropharyngeal cancer

Abstract: The early detection of HCV is important in patients with OPC because this infection may affect their oncologic outcomes. Cancer 2018;124:960-5. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…As we discussed above, HCV might be a doubleedged sword in non-HPV associated HNSCC. Economides et al 18 found that anti-HCV treatment improved the prognosis of HCV-positive HNSCC patients, which is not against our findings. Anti-HCV treatment is mainly based on interferon alpha or direct-acting anti-viral agents (DAA), which both reduce HCV vial loads and stimulate immunity leading a better outcomes for HCVpositive patients.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…As we discussed above, HCV might be a doubleedged sword in non-HPV associated HNSCC. Economides et al 18 found that anti-HCV treatment improved the prognosis of HCV-positive HNSCC patients, which is not against our findings. Anti-HCV treatment is mainly based on interferon alpha or direct-acting anti-viral agents (DAA), which both reduce HCV vial loads and stimulate immunity leading a better outcomes for HCVpositive patients.…”
Section: Discussioncontrasting
confidence: 70%
“…11 However, another retrospective study revealed that HCV infection increased tumor-specific mortality in patients with oropharyngeal cancer (HR = 2.15; 95% CI: 1.08-6.85; P = .02). 18 Besides, the anti-HCV treatment improved the 5-year survival rate of patients with oropharyngeal and oral cancers. 18,19 So far, there were also no investigations about the impact of HCV RNA transcript in the prognosis of non-HPV associated HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 30 However, in patients with oropharyngeal cancers, HCV infection correlated with an increased risk of cancer‐specific death and disease progression. 32 However, the oncologic significance of this is unclear. In our study, anti‐HCV seropositivity had no unfavorable impact on the 5‐year OS and PFS, even in the oropharyngeal subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, in patients with oropharyngeal cancers, HCV infection correlated with an increased risk of cancer-specific death and disease progression. 32 However, the oncologic significance of Cirrhosis was defined based on typical radiologic findings (e.g., hepatic nodularity, massive ascites, and splenomegaly). e Renal impairment was defined as an eGFR < 60 ml/min/1.73 m 2 , calculated with the modification of diet in renal disease equation.…”
Section: Discussionmentioning
confidence: 99%